Characteristics of roe of autumn chum salmon Oncorhynchus keta from the Amur River - A. I. Chepkasova; T. N. Slutskaya; E. I. Barabanshchikov (Известия ТИНРО)
Chemical composition and nutritional and biological value of roe are investigated for autumn chum salmon from the Amur River sampled during their run for spawning from the estuary to the area of Khabarovsk city. Color and strength of roe were examined, content of proteins, lipids and minerals was measured, amino acid and fatty acid composition was determined. Caloric capacity and biological value of the samples were usual for this species. Physical properties of the roe (strength, color intensity) practically did not change in dependence on distance from the river mouth. Stable quality of roe in the run of spawning migration in the lower Amur is concluded.